Biarkan Perempuan Bicara: Analisis Kekuatan Metode Life History dalam Menghadirkan Pengalaman dan Pengetahuan Perempuan dalam Penelitian Ann Goetting - Ita Musarrofa (Sawwa: Jurnal Studi Gender, 2019)
Women's experience and knowledge are two substantive things that must be a concern in order to reconstruct the reality of women, in order to overcome the bias of the roles of men and women in life. This paper aims to examine subjective methods that are able to see the reality of women from the lens of women's experience and knowledge so that women have strategic value in their own lives. This study uses field research methods, with data collection techniques from a variety of narratives of women's life history narratively with life history data analysis techniques. This study produces findings that the method of life history is able to identify the subjective experiences of women in constructing their own reality, based on the root experiences of violence that befell them. Second, women's experiences and knowledge about violence can be utilized as a conscious effort to deal with violence, dare to speak out injustice, and rise from the violence they experienced.